2013
DOI: 10.9745/ghsp-d-12-00049
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the community halfway to reduce maternal deaths? Evidence from a community-based maternal death review in Uttar Pradesh, India

Abstract: Even in the face of vigorous commitment to improving maternal health services in India, inadequate staffing, supplies, and equipment at health facilities, as well as transportation costs and delays in referral, appear to contribute to a substantial proportion of maternal deaths in a representative district in Uttar Pradesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 11 publications
3
10
0
Order By: Relevance
“…Neither time of the emergency, nor location of the pregnant woman, or cost should be factors dissuading families from calling for public referral transport services (31). More than half of the families claim out-of-pocket expenses for transportation and medicines (25). Our study finding corroborates findings such as the reasons given by families for not seeking care; the most common reason was the lack of available transportation.…”
Section: Place Of Death Taken To 1 Facility (%) Taken To 2 Facilitiessupporting
confidence: 82%
See 2 more Smart Citations
“…Neither time of the emergency, nor location of the pregnant woman, or cost should be factors dissuading families from calling for public referral transport services (31). More than half of the families claim out-of-pocket expenses for transportation and medicines (25). Our study finding corroborates findings such as the reasons given by families for not seeking care; the most common reason was the lack of available transportation.…”
Section: Place Of Death Taken To 1 Facility (%) Taken To 2 Facilitiessupporting
confidence: 82%
“…To address this issues, the government of UP may adopt any of the existing models of public referral transport system. However, it is imperative to upgrade the current emergency transport system based on existing IPHS guidelines and bridge the gap in inter-facility transport as needed for Unnao district and the state (12,16,23,25). More importantly, the context and implementation of the public referral transport system should ensure accessibility, availability and readiness.…”
Section: Way Forward For Creating Better Public Referral Transport Sementioning
confidence: 99%
See 1 more Smart Citation
“…As a result, many women are forced to rely on males or senior family members for health decisions (Firoz et al, 2016;Gabrysch & Campbell, 2009;Kyei-Nimakoh, Carolan-Olah, & McCann, 2017;UNDP, 2011;White, Dynes, Rubardt, Sissoko, & Stephenson, 2013). A study in India found that families of deceased women had spent on average seven hours in deciding to take the woman to a facility (Raj, Maine, Sahoo, Manthri, & Chauhan, 2013). Similarly, in Burkina Faso and Indonesia, male relatives of deceased women delayed health seeking until they were in critical condition (D'Ambruoso, Byass, Qomariyah, & Ouedraogo, 2010).…”
Section: The Three Delaysmentioning
confidence: 99%
“…Similarly, in Burkina Faso and Indonesia, male relatives of deceased women delayed health seeking until they were in critical condition (D'Ambruoso, Byass, Qomariyah, & Ouedraogo, 2010). Perceived costs have also been associated with Phase I delays and maternal deaths, especially when families are expected to cover the majority of costs (D'Ambruoso et al, 2010;De Brouwere, Delvaux, & Leke, 2014;Kongnyuy, Mlava, & van den Broek, 2009;Lee et al, 2009;Merali et al, 2014;Raj et al, 2013).…”
Section: The Three Delaysmentioning
confidence: 99%